Numerical simulations of flow past an autonomous underwater vehicle at various drift angles - Gomatam, Sreekar; Vengadesan, S; Bhattacharyya, S K (Journal of Naval Architecture and Marine Engineering, 2012)
Three dimensional (3D) flow past an Autonomous Underwater Vehicle (AUV) is simulated using a Computational Fluid Dynamics (CFD) approach at a Reynolds (Re) number of 2.09x106. A non-linear k-? (NLKE) turbulence model is used for solving the Reynolds Averaged Navier-Stokes (RANS) equations. The effect of control surfaces over the flow, the flow interaction between the hull and the appendages at various Angles of Attack (AoA) and the effect of the symmetry plane is studied. Flow structure, variation of flow variables and force distribution for various AoA are presented and discussed in detail. DOI: http://dx.doi.org/10.3329/jname.v9i2.12567 Journal of Naval Architecture and Marine Engineering 9(2012) 135-152